The antihypertensive profile of the angiotensin AT(1) receptor antagonist, GR138950, and the influence of potential homeostatic compensatory mechanisms in renal hypertensive rats - Anderson, Ian K (1998)
1. The cardiovascular profile of the angiotensin AT(1) receptor antagonist, GR138950, and the influence of potential compensatory homeostatic mechanisms on this profile, were investigated in renal artery ligated hypertensive (RALH) rats. 2. GR138950 caused a marked reduction in blood pressure associated with immediate tachycardia in conscious RALH rats. The antihypertensive action of GR138950 appeared biphasic; an immediate fall in blood pressure, which plateaued within 1 h, and which was followed by a further slow decline that reached maximum between 5–7 h after administration. 3. The tachycardia caused by GR138950 was attenuated by atenolol and was abolished by combined pretreatment with atenolol and atropine methyl nitrate. However, the antihypertensive profile of GR138950 was unchanged by these pretreatments. 4. The resting blood pressure and the antihypertensive effect of GR138950, in RALH rats, were unaffected by the vasopressin V(1) receptor antagonist, [β-mercapto-β,β-cyclopentamethylene propionyl(1)-O-Me-Tyr(2),Arg(8)]-vasopressin. Thus, vasopressinergic mechanisms are not involved in either maintaining blood pressure in RALH rats, or in compensating for the fall in blood pressure caused by GR138950. 5. In anaesthetized RALH rats, GR138950 caused a marked fall in blood pressure that was accompanied by an increase in heart rate along with sustained increases in renal and splanchnic sympathetic nerve activity. 6. In summary, the biphasic fall in blood pressure evoked by GR138950 in RALH rats can not be explained on the basis of changes in autonomic control of the heart, alteration of vasopressin-mediated vasoconstrictor mechanisms or overall suppression of central sympathetic outflow. Rather, increased vasoconstrictor tone might serve to oppose the initial fall in blood pressure.